Programmed Design of a Lithium–Sulfur Battery Cathode by Integrating Functional Units. Issue 17 (19th July 2019) - Zeng, Zhipeng; Li, Wei; Wang, Qiang; Liu, Xingbo
Abstract: Sulfur is considered to be one of the most promising cathode materials due to its high theoretical specific capacity and low cost. However, the insulating nature of sulfur and notorious "shuttle effect" of lithium polysulfides (LiPSs) lead to severe loss of active sulfur, poor redox kinetics, and rapid capacity fade. Herein, a hierarchical electrode design is proposed to address these issues synchronously, which integrates multiple building blocks with specialized functions into an ensemble to construct a self‐supported versatile cathode for lithium–sulfur batteries. Nickel foam acts as a robust conductive scaffold. The heteroatom‐doped host carbon with desired lithiophilicity and electronic conductivity serving as a reservoir for loading sulfur can trap LiPSs and promote electron transfer to interfacial adsorbed LiPSs and Ni3 S2 sites. The sulfurized carbon nanofiber forest can facilitate the Li‐ion and electron transport and retard the LiPSs diffusion as a barrier layer. Sulfiphilic Ni3 S2 acts as both a chemical anchor with strong adsorption affinity to LiPSs and an efficient electrocatalyst for accelerating kinetics for redox conversion reactions. Synergistically, all functional units promote the lithium ion coupled electron transfer for binding and redox conversion of LiPSs, resulting in high reversible capacities, remarkable cycle stability, and excellent rate capability. Abstract : The insulating nature, high solubility, and polarity of lithium polysulfides seriously hinder the practical application of lithium–sulfur batteries. Herein, a bioinspired hierarchical electrode architecture design is developed to integrate multiple functional units of sulfur reservoir, chemical anchors, electrocatalysts, and conductive framework into an ensemble to obtain a versatile and high‐performance cathode. The cathode exhibits excellent cycling and rate performances.